3D projection electrophoresis for single-cell immunoblotting - Samantha M. Grist (Nature Portfolio, 2020)
Single-cell immunoblotting previously separated proteins on a polyacrylamide slab in the xy direction and was limited by throughput and sample consumption. Here the authors adapt the system to separate proteins in the z direction, allowing for closer spacing of sample wells and improved sample consumption.